Post-Schooling Human Capital Investments and the Life Cycle of Earnings - Magnac, Thierry; Pistolesi, Nicolas; Roux, Sébastien (Journal of Political Economy, 2018)
We propose an original model of human capital investments after leaving school in which individuals differ in their initial human capital obtained at school, their rates of return and costs of human capital investments, and their terminal values of human capital at an arbitrary date in the future. We derive a tractable reduced-form Mincerian model of log earnings profiles along the life cycle that is written as a linear factor model in which levels, growth, and curvature of earnings profiles are individual specific. This provides a structural interpretation of results obtained in the empirical literature on the dynamics of earnings and acknowledges its limitations.